Performance of Interse Merawangarab and Arabmerawang Chicken Cross at Age 1 to 10 Weeks - Nurcahya Nurcahya; S. Darwati; P. Rohmatulloh (Universitas Nasional Jakarta, 2022)
Indonesia have many local chicken, such as merawang chicken and arab chicken. Arab chickens are layer local chicken that has egg production more than merawang chicken. Crossing between merawang arab chicken and arab merawang chicken aimed to improve genetic quality through heterosis effect. Interse of merawangarab (MAMA) with interse of arab merawang (AMAM) were observed for their production traits. Total of 98 MAMA chickens and 46 AMAM chickens were observed for their body weight, feed consumption, feed conversion and mortality.This research used covariance (ANCOVA) in randomized complete block designed (RAK). Chicken crossing as a treatment and concomitant is DOC weight. The body weight of MAMA and AMAM were not different (P>0.05). Body weight MAMA male and female at age 10 weeks were 843.10 g and 763.5 g respectively. Body weight AMAM male and female at age 10 weeks were 825.82 g and 741.2 g respectively. Feed intake and feed conversion of MAMA and AMAM male were not different (P>0.05) as well as MAMA and AMAM female. Mortality were occurred in early rearing phase of AMAM chicken was 2.2%. Performance of MAMA and AMAM chicken at age 1-10 weeks were same.